Studying Intention to Use Sharia E-Commerce on Generation Z Muslims in Central Java Using Technology Acceptance Model and Extended Theory of Planned Behaviour - Bih, Kafa; Maharani, Dita Indah (Invest Journal of Sharia & Economic Law, 2025)
This study analyzes the factors influencing Sharia e-commerce adoption among Generation Z Muslims in Central Java using the Technology Acceptance Model and Extended Theory of Planned Behavior. Data collected from 125 respondents were analyzed using SmartPLS. The results show that all constructs positively influenced the intention to use Sharia e-commerce. Perceived Ease of Use had the greatest influence on Perceived Usefulness, followed by Ihsan and religiousness on attitudes Towards behavior. The integration of Ihsan and religiosity reflects the role of religious values in shaping e-commerce attitudes among Generation Z. From an institutional economics perspective, religiosity and Ihsan function as informal institutions that direct economic behavior. The bounded rationality framework shows that individuals are influenced by social and religious values during decision making. These findings encourage e-commerce players to consider transparency, security, and compliance with Sharia. Policymakers should support Sharia e-commerce guidelines and incentivize ethical digital platforms. Collaboration among regulators, Islamic financial authorities, and the National Sharia Council is needed for uniform digital economy standards.